Power allocation optimization for oam-mimo systems with unaligned antennas - Xiong, Xusheng; Li, Qiang; Ge, Xiaohu; Sali, Aduwati; Mohd Ali, Borhanuddin (Institute of Electrical and Electronics Engineers, 2022)
Crosstalk among different orbital angular momentum (OAM) states, mainly caused by the atmospheric turbulence and the misalignment between the transmitting and receiving antennas, leads to the increase of error probability of OAM transmission systems. Considering the OAM-based multiple-input multiple-output (OAM-MIMO) transmission system with unaligned antennas, the error probability model is derived under the non-Kolmogorov turbulence. Furthermore, a power allocation optimization algorithm is proposed to alleviate the crosstalk among different OAM states, thus effectively decreasing the error probability of the OAM-MIMO transmission system. Numerical results show that the error probability reduction of the OAM-MIMO transmission system by using the proposed optimization algorithm is up to 26.1 dB.